Recent application of carbon nanotubes in energy storage and conversion devices - Abdulazeez Tunbosun Lawal (Carbon Trends)
Worldwide energy demand is increasing at an unprecedented rate due to rapid population growth and industrialization. Hence, renewable and environmentally friendly energy production platforms are more needed than ever as alternatives to fossil fuels, which is a critical societal dilemma. The superior mechanical, electrical, thermal, and electrochemical properties of Carbon nanotubes (CNTs) make them a promising next-generation material for energy conversion and storage applications. CNTs can be synthesized using various methods, such as chemical vapor deposition, laser ablation, and carbon arc discharge. Each of their properties makes them an ideal candidate for various energy conversion and storage devices. Moreover, the performance of CNTs in these energy devices can be improved by surface functionalization, heteroatom doping, structural modification, introductions of defects, promoting transport hydrodynamic processes, and resolving existing degradation issues, such as catalyst poisoning and precipitation. Owing to their highest specific capacitance, enhanced rate capability, and extended cycle life, CNTs have been used in electrochemical energy storage systems, such as supercapacitors, batteries, and supercapattery, as well in energy conversion platforms, such as fuel cells, microbial fuel cells, and solar cells. Since CNTs are emerging as a technologically promising multi-functional nanomaterial due to their unique nanostructure and physical and chemical properties, this review also covers the challenges in realizing the full potential of CNTs for our energy storage and conversion technologies, together with future research directions needed to optimise their structure, properties and functionalisation.